Memorandum of understanding between Universiti Teknologi MARA and Bolt Studio Sdn Bhd / Fakulti Filem, Teater dan Animasi - Universiti Teknologi MARA, Fakulti Filem, Teater dan Animasi (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship and cooperation for friendship, cooperation and collaboration.